1999
DOI: 10.4049/jimmunol.162.5.2775
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Cycle Progression by Rapamycin Induces T Cell Clonal Anergy Even in the Presence of Costimulation

Abstract: Costimulation (signal 2) has been proposed to inhibit the induction of T cell clonal anergy by either directly antagonizing negative signals arising from TCR engagement (signal 1) or by synergizing with signal 1 to produce IL-2, which in turn leads to proliferation and dilution of negative regulatory factors. To better define the cellular events that lead to the induction of anergy, we used the immunosuppressive agent rapamycin, which blocks T cell proliferation in late G1 phase but does not affect costimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…First, our results show that NK cells exposed to atRA were unable to efficiently engage mTORC1 and increase cMyc expression in response to IL-18. mTORC1 and cMyc are metabolic regulators that increase glycolysis rate and support pro-inflammatory effector responses in T cells (Powell, Lerner, & Schwartz, 1999; R. Wang et al, 2011; Zheng et al, 2007). NK cells require mTORC1 for development, as well as for the IL-15-induced IFN-γ production by elevating glycolytic rate (Marcais et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…First, our results show that NK cells exposed to atRA were unable to efficiently engage mTORC1 and increase cMyc expression in response to IL-18. mTORC1 and cMyc are metabolic regulators that increase glycolysis rate and support pro-inflammatory effector responses in T cells (Powell, Lerner, & Schwartz, 1999; R. Wang et al, 2011; Zheng et al, 2007). NK cells require mTORC1 for development, as well as for the IL-15-induced IFN-γ production by elevating glycolytic rate (Marcais et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 78 This donor-derived hematopoiesis has been shown sufficient to reverse the SCD phenotype. 77 , 78 , 79 A low level of irradiation, together with rapamycin use, has been shown to suppress the immune response and prevent the occurrence of graft-versus-host disease. 79 , 80 In our SCD mouse transplantation studies, we achieved 36% ± 6% engraftment of donor cells in the bone marrow (data not shown), which is consistent with results in a recent report.…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 78 , 79 A low level of irradiation, together with rapamycin use, has been shown to suppress the immune response and prevent the occurrence of graft-versus-host disease. 79 , 80 In our SCD mouse transplantation studies, we achieved 36% ± 6% engraftment of donor cells in the bone marrow (data not shown), which is consistent with results in a recent report. 81 Because cytokine pretreatment could induce HSC differentiation and loss of long-term repopulating activity, 82 in our protocol, mouse HSCs were directly incubated with lentivirus without cytokine prestimulation before gene transduction.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR likely prevents anergy induction by IL-2 expression in T cells. A previous study found that by blocking mTOR with rapamycin, the cell cycle of clonal T cells was inhibited, while it induced cell anergy even with costimulations ( 101 ). In the process of naïve T cell differentiation, mTOR mediates the transformation to Th17 or Treg cells by altering the sensitivity of T cells to TGF-β, which influences the effects of STAT3 signaling ( 102 ).…”
Section: Experimental Therapeutic Strategies Of Ssmentioning
confidence: 99%